2021
DOI: 10.35845/kmuj.2021.20602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Canagliflozin Alone and in Combination With Metformin on Hormonal Derangements and Estrous Cycle in a Polycystic Ovary Syndrome Rat Model

Abstract: To evaluate the effect of canagliflozin and metformin on the estrous cycle and hormonal derangement of letrozole induced polycystic ovarian syndrome (PCOS) in Sprague Dawly rats. METHODS:Thirty six female adult non-pregnant Sprague Dawly rats were divided into six groups and all, except normal control (A), were treated with letrozole 1mg/kg daily for 21 days. Treatment was started to all rats except normal control (group-A) and disease control (group-B). Canagliflozin 10 mg/kg, metformin 100 mg/kg and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…They also showed that the number of granulosa cells and the production of lutein were significantly improved in the metformin‐treated group, while cystic follicle enlargement was missing. Our findings are consistent with those of Zaheer et al., 2021, who examined the impact of canagliflozin and metformin on the estrous cycle and hormonal dysregulation of letrozole‐induced PCOS in rats and came to the conclusion that canagliflozin is effective alone and enhances the impact of metformin in the regulation of estrous cycles and reversal of hormonal disturbances in a rat model of PCOS. According to reports, canagliflozin enhances B‐cell activity by lowering insulin demand and hyperinsulinemia, which are major contributors to the rise in testosterone levels in PCOS.…”
Section: Discussionsupporting
confidence: 92%
“…They also showed that the number of granulosa cells and the production of lutein were significantly improved in the metformin‐treated group, while cystic follicle enlargement was missing. Our findings are consistent with those of Zaheer et al., 2021, who examined the impact of canagliflozin and metformin on the estrous cycle and hormonal dysregulation of letrozole‐induced PCOS in rats and came to the conclusion that canagliflozin is effective alone and enhances the impact of metformin in the regulation of estrous cycles and reversal of hormonal disturbances in a rat model of PCOS. According to reports, canagliflozin enhances B‐cell activity by lowering insulin demand and hyperinsulinemia, which are major contributors to the rise in testosterone levels in PCOS.…”
Section: Discussionsupporting
confidence: 92%